PEMBINAAN MUTU GURU MELALUI PROGRAM SERTIFIKASI DAN PENILAIAN KINERJA GURU PADA DINAS PENDIDIKAN KABUPATEN KUTAI TIMUR - Khusnul Wardan (Al-Rabwah, 2019)
This study aims to describe the Teacher Quality Development Through Certification and Teacher Performance Evaluation Programs at the East Kutai District Education Office in East Kalimantan. The approach used in this study is phenomenological qualitative, meaning that the researcher tries to photograph, analyze and construct the situation of the teacher and the environment as subjects as well as research respondents. Data collection method by interview. Data analysis techniques used qualitative data analysis techniques for the Miles and Huberman models, namely data reduction, data display and withdrawal / verification or conclusions. The results of the study showed that teacher quality training through the certification program was going well. First, the implementation of the teacher certification program in East Kutai still runs in a different pattern than in previous years. Secondly, there are still many found in the field of the use of certification fund allocation is not as expected. Third, post certification certification by the East Kutai District Education Office is still lacking. This post-certification teacher training needs to be done because not all teachers who have finished certification carry out what they have gotten at the time of the certification training. From the interview results, we can conclude about the implementation of Teacher Performance Assessment (PKG) at the East Kutai District Education Office as follows. First, the implementation of Teacher Performance Assessment by principals and assessors has been going well, this is illustrated from the results of observations and interviews in all field sources was asked to answer that they had been rated by their principals and assessors from senior teacher elements. Second, based on the data in the field there are still many teachers who do not know what components are assessed in the implementation of Teacher Performance Assessments by school principals, Third, school principals need to evaluate the implementation of Teacher Performance Assessments that have been carried out.